Frederick Sanger Two-Time Nobel Laureate in Chemistry - Jeffers, Joe S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this Brief, Joe Jeffers uncovers the life and works of two-time Nobel Laureate Frederick Sanger. Following Sanger's early life to retirement, Jeffers describes how this celebrated British biochemist became the first person to determine the amino acid sequence of a protein for which he was awarded the Nobel Prize in 1958. Highlighting Sanger's remarkable career, Jeffers describes Sanger's later change in research direction to investigate deoxyribonucleic acids (DNA), work for which Sanger also received the Nobel Prize jointly with Paul Berg and Walter Gilbert in 1980. Joe Jeffers conducted twelve interviews with Sanger over the period of 1999-2009 and he has also spoken to more than 40 of Sanger's colleagues and family members. This brief provides a rigorous yet concise view of Sanger on a personal and scientific level and is suitable for biochemists, historians or the interested layperson.
Introduction -- Early Life 1918-1943 -- Protein Period 1943-1962 -- Origins of the Medical Research Council Laboratory of Molecular Biology.- RNA Period 1962-1971 -- DNA Period 1969-1983 -- Life outside the Lab -- The Man and His Legacy.
Keywords: Bioorganic chemistry; Science -- History; Proteins .; Bioorganic Chemistry; History of Science; Protein Biochemistry